2018
DOI: 10.18178/ijmmm.2018.6.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of Robotic Surface Finishing Using Abrasive Disc

Abstract: This study is based on the optimization of process parameters in abrasive robotic finishing process. The effect of certain process parameters on the surface finish of the abraded surface is to be studied using Design of Experiments (DOE) methodology. The finishing or polishing operation is vital in any manufacturing processes. Methods have evolved from hand finishing operations to automatic finishing using CNC machines used currently. This research pertains to the next level of finishing with the usage of a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The results maintain the same value for the surface finish of brass, 0.44 µm, tripling productivity, and keeping the force level at its minimum value. Unlike the study in [ 22 ], the level of roughness obtained with the sanding process is not affected by an increase in the feed rate, in a “saturated state”. This is the main outcome from this work because it will allow optimizing of the process parameters in future sanding tasks with a collaborative robot.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The results maintain the same value for the surface finish of brass, 0.44 µm, tripling productivity, and keeping the force level at its minimum value. Unlike the study in [ 22 ], the level of roughness obtained with the sanding process is not affected by an increase in the feed rate, in a “saturated state”. This is the main outcome from this work because it will allow optimizing of the process parameters in future sanding tasks with a collaborative robot.…”
Section: Discussionmentioning
confidence: 76%
“…However, other works provide more complex mathematical models that allow obtaining of the minimum number of passes and the characteristics of the abrasive material that should be used to obtain the desired roughness [ 11 , 21 ]. An experimental investigation was developed in [ 22 ], from which the parameters that affect the surface quality in an industrial robot (no collaborative) polishing could be obtained. From this work, it was concluded that the geometry of the workpiece and the cutting speed do not contribute significantly to the roughness response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main applications of this software are related to processes where forces must be controlled. The main applications are force monitoring in the processes of machining [12] or polishing [13][14][15]. Robotic joining technologies in which forces play an important role also make extensive use of the capabilities of the Test Signal Viewer software.…”
Section: State Of Knowledgementioning
confidence: 99%